Thermal and Sound Absorption Properties of Porous Epoxy Resin Modified by Organic Silicon. Issue 1 (March 2021) - Gou, Xiaobin; Peng, Longgui; Wu, Siyuan; Du, Lifei; He, Qirui; Zhao, Pu
Abstract: The organic silicon modified epoxy resin is prepared by the dehydration reaction between diphenyl silicon diol and the hydroxyl group on the epoxy resin, and the foamed material is prepared by the mass ratio NaHCO3:H:OBSH=5:5:3 composite foaming agent. The foams was characterized by infrared spectroscopy (FT-IR), Thermogravimetric (TG) and standard wave tube method. The results indicate that: The heat resistance of the cured resin of modified resin is better than that of cured epoxy resin, and the sound absorption coefficient of the sample with opening rate of about 54.4% can reach more than 0.8 for high frequency sound waves (>1000 Hz).